Artificial Intelligence in Medical Imaging and Image Processing (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Reprint discusses the increasing significance of computer-aided diagnosis in modern healthcare, emphasizing its benefits for both medical professionals and patients. It highlights the growing role of automation in supporting human tasks, particularly in image analysis, facilitated by artificial intelligence (AI) networks capable of performing multilayer pattern analyses. AI algorithms aid image segmentation, class assignment, and result description, leading to the standardization of diagnostic processes and optimalization of workflows. The implementation of AI enhances medical specialists' efficiency, thereby improving healthcare quality. The proposed selection of scientific papers presents the diversity of AI approaches and techniques for various computing systems, focusing on their applications in diagnostic imaging within the medical field. This Reprint aims to present current knowledge on AI methods in medical systems, fostering the exchange and understanding of AI's technical aspects and applications in modern radiology and medical image processing.